Analisis Penggunaan Media Loose Part untuk Meningkatkan Kemampuan Motorik Halus Anak Usia 5-6 Tahun - Ridwan, Ahmad; Nurul, Nurul Azian; Faniati, Fenny (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2022)
The interest of a child in the learning process becomes an important factor that the teacher must pay attention to. The child’s disinterest in the learning process results in the child’s development, especially the child’s motor, being hampered. This study, in accordance, aims to realize the use of loose part media to improve the fine motor skills of children aged 5-6 years in group B of Pembina State Kindergarten, Tembilahan. This research uses a qualitative approach, where data was collected by using structured interview techniques and documentation. The informants in this study were the class teacher and the accompanying teacher. The data were analyzed using Miles and Huberman model data triangulation. The results showed that the media loose part was always used in the learning process. This is due to its flexibility in every lesson, its ease of use in games, and its liking to the child.  In addition, this also gives freedom to children to put their idea, creativity, and imagination into the activity.